Ginger from Farmyard to Town: Nutritional and Pharmacological Applications - Unuofin, Jeremiah Oshiomame; Masuku, Nelisiwe Prenate; Paimo, Oluwatomiwa Kehinde; Lebelo, Sogolo Lucky (Frontiers in Pharmacology, 2021)
Ginger (Zingiber officinale) is one of the most widely used natural products consumed as a spice and medicine for treating diabetes, flatulent intestinal colic, indigestion, infertility, inflammation, insomnia, a memory booster, nausea, rheumatism, stomach ache, and urinary tract infections. To date, over 400 bioactive components, such as diarylheptanoids, gingerol analogues, phenylalkanoids, sulfonates, monoterpenoid glycosides, steroids, and terpene compounds have been derived from ginger. Increasing evidence has revealed that ginger possesses a broad range of biological activities, especially protective effects against male infertility, nausea and vomiting, analgesic, anti-diabetic, anti-inflammatory, anti-obesity, and other effects. The pharmacological activities of ginger were mainly attributed to its active phytoconstituents such as 6-gingerol, gingerdiol, gingerol, gingerdione, paradols, shogaols, sesquiterpenes, zingerone, besides other phenolics and flavonoids. In recent years, in silico molecular docking studies revealed that gingerol (6-gingerol, 8-gingerol, and 10-gingerol) and Shogaol (6-shogaol, 8-shogaol, 10-shogaol) had the best binding affinities to the receptor protein in disease conditions such as diabetes, inflammation, obesity, and SARS-CoV-2. Furthermore, some clinical trials have indicated that ginger can be consumed for alleviation of nausea and vomiting induced by surgery, pain, diabetes, obesity, inflammation, male infertility. This review provides an updated understanding of the scientific evidence on the development of ginger and its active compounds as health beneficial agents in future clinical trials.